2020
DOI: 10.3390/ijms21144828
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous FTIR and Raman Spectroscopy in Endometrial Atypical Hyperplasia and Cancer

Abstract: Currently, endometrial carcinoma (EC) is the most common genital cancer in high-income countries. Some types of endometrial hyperplasia (EH) may be progressing to this malignancy. The diagnosis of EC and EH is based on time consuming histopathology evaluation, which is subjective and causes discrepancies in reassessment. Therefore, there is a need to create methods of objective evaluation allowing the diagnosis of early changes. The study aimed to simultaneously asses Fourier Transform Infrared (FTIR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 43 publications
(48 reference statements)
0
18
0
Order By: Relevance
“…The difficulties of differential diagnosis of prostate cancer and precancerous processes contribute to the development and introduction into clinical practice of the latest diagnostic methods based on the use of high-tech and sensitive equipment. At present, reports on the use of laser optical spectroscopy in the diagnosis of a wide number of diseases are increasingly appearing in the world literature [ 5 , 38 , 39 , 40 , 41 , 42 , 43 ]. Compared to traditional imaging methods (Magnetic Resonance Imaging and Transrectal Ultrasound Diagnostics), optical methods have a number of unique advantages.…”
Section: Discussionmentioning
confidence: 99%
“…The difficulties of differential diagnosis of prostate cancer and precancerous processes contribute to the development and introduction into clinical practice of the latest diagnostic methods based on the use of high-tech and sensitive equipment. At present, reports on the use of laser optical spectroscopy in the diagnosis of a wide number of diseases are increasingly appearing in the world literature [ 5 , 38 , 39 , 40 , 41 , 42 , 43 ]. Compared to traditional imaging methods (Magnetic Resonance Imaging and Transrectal Ultrasound Diagnostics), optical methods have a number of unique advantages.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, Raman and FTIR spectroscopy can be used to obtain information about chemical changes. Importantly, our previous study demonstrated the potential of FT-Raman and FTIR spectroscopy for the identification of chemical changes in atypical complex hyperplasia and endometrioid adenocarcinoma cancer 4 . To the best of our knowledge, this is the first study applying physical methods such as FT-Raman and FTIR spectroscopy with multidimensional analysis and correlation test to evaluate carcinogenesis in endometrial cancer.…”
Section: Introductionmentioning
confidence: 97%
“…Spectroscopy candidates for this role. Specimens for both pathological spectroscopic analysis of stages of endometrial cancer carcinogenesis and tissues adjacent cancer are easily available in curettage 4 . Another aim of spectroscopic analysis of stages preceding endometrial cancer may be to determine a new mechanism operating behind the initiation of carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations